Estimation of Adequate Life insurance: A Case study - Dr. Swamy TNVR ,Dr. Rajesh Mamilla (International Journal of Advanced Science and Technology, 2020)
Mr. Thomas having age of 35 years, working with a renowned company in Hyderabad, India. He is doing as a Production head for the last six years after completing his M.Tech, from a reputed engineering Institute in Hyderabad. He was married four years back and his wife was a home-maker. He had a two years old daughter. They were not planning for a second child. His parents were not dependent on him. Thomas was an ambitious and highly motivated young man. As a part of his job training, recently Thomas had attended one Executive Development Programme (EDP) in Delhi on “Work Life Balance” for a period of two months. As a part of the EDP, under the concept of Life Insurance for family protection, he came to know why Life Insurance is so important in Human Life Value. The objective of the programme was to educate the young Indians about the urgency and importance of life insurance planning and risk management and encourage them to buy adequate life insurance cover. Thomas was highly impressed with five reasons as shown below